PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PADA KOPERASI SERBA USAHA BALIEM ARABICA DI KABUPATEN JAYAWIJAYA - KENELAK, DINUS; PIO, RIANE JOHNLY; KAPARANG, SONNY GERSON (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract. This study aims to determine the effect of compensation on the employee's performance of business cooperatives Baliem Arabica in Jayawijaya. To test the effect of compensation to employee performance correlation and regression analysis was used with a total sample of 39 respondents. The results showed there is a compensation effect on employee performance. Therefore, the board of Baliem Arabica business cooperatives should pay attention to the compensation granted to employees in order to have a positive impact on the sustainability of the business in the future. Keywords: Compensation, Employee Performance